Personality and the use of cancer screenings: results of the German National Cohort - Hajek, André; Becher, Heiko; Brenner, Hermann; Holleczek, Bernd; Katzke, Verena; Kaaks, Rudolf; Minnerup, Heike; Karch, André; Baurecht, Hansjörg; Leitzmann, Michael; Peters, Annette; Gastell, Sylvia; et al. (Preventive Medicine Reports, 2024)
Objective - To determine the association between personality characteristics and use of different cancer screenings. - Methods - We used data from the German National Cohort (NAKO; mean age was 53.0 years (SD: 9.2 years)) - a population-based cohort study. A total of 132,298 individuals were included in the analyses. As outcome measures, we used (self-reported): stool examination for blood (haemoccult test, early detection of bowel cancer), colonoscopy (screening for colorectal cancer), skin examination for moles (early detection of skin cancer), breast palpation by a doctor (early detection of breast cancer), x-ray examination of the breast (“mammography”, early detection of breast cancer), cervical smear test, finger examination of the rectum (early detection of prostate cancer), and blood test for prostate cancer (determination of Prostate-Specific Antigen level). The established Big Five Inventory-SOEP was used to quantify personality factors. It was adjusted for several covariates based on the Andersen model. Unadjusted and adjusted multiple logistic regressions were computed. - Results - A higher probability of having a skin examination for moles, for example, was associated with a higher conscientiousness (OR: 1.07, p < 0.001), higher extraversion (OR: 1.03, p < 0.001), higher agreeableness (OR: 1.02, p < 0.001), lower openness to experience (OR: 0.98, p < 0.001) and higher neuroticism (OR: 1.07, p < 0.001) among the total sample. Depending on the outcome used, the associations slightly varied. - Conclusions - Particularly higher levels of extraversion, neuroticism and conscientiousness are associated with the use of different cancer screenings. Such knowledge may help to better understand non-participation in cancer screening examinations from a psychological perspective.
Gesehen am 16.12.2024